Nested pathways to adaptation. (4th February 2019) - Chhetri, Netra; Stuhlmacher, Michelle; Ishtiaque, Asif
Abstract: Societies around the world have shown a strong capacity for responding to climatic and other stresses throughout history. Based on the large body of literature on adaptation to both climatic and other stresses, this paper examines the scalar interconnections and nested hierarchical nature of adaptation decision. Drawing on case studies from around the world, we propose three stages of nested adaptation: (a) coping with change, (b) incremental adjustment to manage risk, and (c) system transformation. The effectiveness of coping is often marginal but forms benchmarks against which future adaptation to climate change can be assessed. Incremental adaptations, largely associated with technological fixes, involve more exogenous actors and operate at a greater scale than coping. Transformational adaptation is expected to occur when the rate and magnitude of change threatens to overwhelm the system. Nested with multiple-scale spatial hierarchy, the three pathways to climate adaptation are interconnected; understanding the cross-scale interactions, feedback loops and the spatial and temporal dynamics within the hierarchy is important because it affects planning and policy integration, including allocation of financial resources.